Howard Howe’s Self-Destruction in Kevin Smith’s Movie Script Tusk (2014) - Sherlly Margaretha (Menulis: Jurnal Penelitian Nusantara, 2026)
The purpose of this thesis is to determine how misanthropy is portrayed in Kevin Smith's film Tusk. In this film, misanthropy is seen through the character Howard Howe, who harbors hatred and disappointment towards humans due to his life experiences. This study uses a qualitative method with a descriptive approach to explain the characteristics, causes, and effects of misanthropy as shown in the film. The main causes of Howard's misanthropy are trauma, betrayal, and failed expectations of humanity. As the story progresses, the character's misanthropic nature becomes increasingly clear through dialogue, actions, and symbols. The representation of misanthropy in this film is shown through the rejection of humans and the glorification of animals, especially walruses. Thus, the film Tusk shows the dark side of human psychology and the consequences of losing trust in others.